Case report: Open bite as an extrapyramidal side effect with aripiprazole, a dopamine partial agonist - Sumi, Satoko; Nagamine, Takahiko; Sumi, Koji; Aijima, Reona; Oka, Kyoko; Toyofuku, Akira (Frontiers in Psychiatry, 2022)
Long-term, fixed-point posttreatment observation of orthodontically treated patients provided us with the opportunity to capture the onset, development, and improvement of open bite, a type of malocclusion. Based on the chronological sequence of events, i.e., a tendency for open bite to worsen with increasing aripiprazole dosage and to improve with decreasing dosage, it was inferred that the onset of malocclusion was caused by extrapyramidal symptoms related to aripiprazole dosage. Physicians should be aware of this side effect when prescribing aripiprazole to children and adolescents. Careful consideration of medication history is necessary when dentists treat open bite in children and adolescents.